Mortality attributable to cigarette smoking in the United States - Rogers, R. G.; Hummer, R. a.; Krueger, P. M.; Pampel, F. C.
tbls.
pp. 259-292
Keywords: Estados Unidos de America; Mortalidad; Tabaco